Restructuring in the global economy: The consequences of strategic linkages between Japanese and U.S. firms - Hurry, Dileep (Strategic Management Journal, 1993)
Global corporate restructuring often involves U.S. and Japanese alliance partners in interlinked portfolio choices. This paper develops theory and propositions that study U.S. and Japanese restructuring as a process of strategic choice, and introduces the concept of the restructuring profile. Japanese-U.S. strategic linkages create choices in the form of a call option on portfolio reconfiguration for the Japanese firm, and a put option on financial restructuring for its U. S. partner. While Japanese competition forms an initiating force for U. S. restructuring, it also offers a source of capital for that purpose-a unique situation in which the Japanese firm is a part of both the problem and the solution in its U. S. partner's restructuring.